(untitled) (ENTHYMEMA, 2020)
After introducing the main theme of the section “Italian Contemporary Poetry: methodological hypothesis and historiographical investigations”, this article calls into question long-established paradigms in the critical debate on poetry: the fragmentary nature of recent poetic production, and ideological disorientation. These topoi are often underpinned by a negative attitude towards pluralism and involve a nostalgic and one-dimensional conceptualization of tradition. By contrast, new routes for the historical and stylistic investigations of the poetic text may be opened thanks to the anti-essentialist concept of resource and a positive and adventurous idea of pluralism. The article then goes on to offer an overview of the first set of papers, which are mostly oriented towards theoretical and methodological innovation.